Perempuan dan Liminalitas dalam Tradisi Perkawinan Adat di Timor Tengah Selatan - Marsel Eliaser Liunokas (Universitas Negeri Medan, 2020)
Timorese culture is patriarchal in that men are more dominant than women. As if women were not considered in traditional rituals so that an understanding was built that valued women lower than men. However, in contrast to the article to be studied, this would like to see the priority of women’s roles in traditional marriages in Belle village, South Central Timor. The role of women wiil be seen from giving awards to their parents called puah mnasi manu mnasi. This paper aims to look at the meaning of the rituals of puah mnasi maun mnasi and the role and strengths that women have in traditional marriage rituals in the village of Belle, South Central Timor. The method used for this research is a qualitative research method using interview techniques with a number of people in the Belle Villa community and literature study to strengthen this writing. Based on the data obtained this paper shows that the adat rituals of puah mnasi manu mnasi provide a value that can be learned, namely respect for women, togetherness between the two families, and brotherhood that is intertwined due to customary marital affrairs.